TEKNIK BUZZ GROUP DAN TEKNIK GROUP EXERCISES SEBAGAI STRATEGI MENINGKATKAN SELF-EFFICACY PENGAMBILAN KEPUTUSAN KARIR - muhamad ayub (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2023)
The purpose of this study was to test the effectiveness of the buzz group technique and group exercises technique to increase self-efficacy in making career decisions for students of MAN 1 Kota Serang. The experimental design method used in this study was the "Randomized Pretest-Postest Comparison Group Design" experimental design. The subjects of this study were 30 students who had a low self-efficacy category of career decision making selected from 300 students. Purposive was done to place 10 students into three experimental groups. This study used a data collection tool on the career decision self-efficacy–tarumanegara scale. The data analysis uses Kruskal Wallis. The results of this study indicate that the buzz group technique and group exercises technique are effective in increasing students' self-efficacy in making career decisions. This is based on the effect shown by each technique from the results before and after treatment. Based on the results of the study, it can be concluded that the two techniques are effective in increasing the self-efficacy of student career decision making. Suggestions are given to school counselors to be able to carry out group buzz group techniques and group exercises techniques to increase students' self-efficacy in making career decisions. In addition, it is hoped that this research can be developed with new characteristics and findings.